BUILDING MULTICULTURAL-BASED ENTREPRENEURSHIP EDUCATION: A CURRICULUM REVIEW - Sholeh, Ahmad; Priatmoko, Sigit; Sugiri, Wiku Aji; Faizah, Maryam (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 3 No 1 (2022): Proceeding of International Conference on Engineering, Technology, and Social Sciences, 2023)
Entrepreneurial skills have become a hot issue in the world of education. Revised: lately. It indicated that mastery of these skills could reduce education unemployment rate. In today's global era, entrepreneurial skills need to be supported by multicultural awareness. Thus, students are better prepared to face international competition in the future. This study aims to describe the process of developing a multicultural-based entrepreneurship curriculum in high schools. This study used a qualitative method with a multisite design. The results showed that the two research sites' entrepreneurship curriculum was designed to provide broad opportunities for students to develop entrepreneurial skills through direct experience according to their respective talents and interests. Various facilities are equipped to support the application of this curriculum model. Multicultural awareness is positioned as a hidden curriculum and is taught through school culture, spiritual honing, educator role models, and students' involvement in academic and non-academic activities. The entrepreneurial learning process emphasizes direct experience. Students are involved in entrepreneurial practices run by the school.